Joint encryption and error correction schemes: A survey - Chothe, R. V.; Ugale, S. P.; Chandwadkar, D. M.; Shelke, S. V. (IAES Indonesian Section, 2024)
In this recent era, the sharing of critical information is essential. Along with information security, error-free data transmission is equally important. Crypto-coding is the method combining encryption algorithms and error correcting codes to enhance performance in terms of security, time, resources, or complexity. Despite the significant research, a comprehensive systematic literature survey that explores the status of research is not available. The proposed study fills this gap by exploring the available research in detail and highlighting past contributions, allowing readers and upcoming researchers to have a detailed understanding of various software and hardware implementations of crypto-coding algorithms and their results. This paper presents a comparison of encryption methods based on various parameters. The crypto-coding research work in satellite communication is also added. The survey includes implementation methods, results, applications, and comparisons of previous work results. This systematic literature survey also covers open issues and future trends of solutions in this context. The paper will offer directions for potential research in the area of crypto-coding and will expand the research frame for upcoming scholarly research.